Dynamics of Monolayer–Island Transitions in 2, 7‐Dioctyl‐benzothienobenzthiophene Thin Films. Issue 11 (27th May 2013) - Dohr, Michael; Werzer, Oliver; Shen, Quan; Salzmann, Ingo; Teichert, Christian; Ruzié, Christian; Schweicher, Guillaume; Geerts, Yves Henri; Sferrazza, Michele; Resel, Roland
Abstract The order in molecular monolayers is a crucial aspect for their technological application. However, the preparation of defined monolayers by spin‐coating is a challenge, since the involved processes are far from thermodynamic equilibrium. In the work reported herein, the dynamic formation of dioctyl‐benzothienobenzothiophene monolayers is explored as a function of temperature by using X‐ray scattering techniques and atomic force microscopy. Starting with a disordered monolayer after the spin‐coating process, post‐deposition self‐reassembly at room temperature transforms the initially amorphous layer into a well‐ordered bilayer structure with a molecular herringbone packing, whereas at elevated temperature the formation of crystalline islands occurs. At the temperature of the liquid‐crystalline crystal–smectic transition, rewetting of the surface follows resulting in a complete homogeneous monolayer. By subsequent controlled cooling to room temperature, cooling‐rate‐dependent kinetics is observed; at rapid cooling, a stable monolayer is preserved at room temperature, whereas slow cooling causes bilayer structures. Increasing the understanding and control of monolayer formation is of high relevance for achieving ordered functional monolayers with defined two‐dimensional packing, for future applications in the field of organic electronics.